2020
DOI: 10.3390/su12156090
|View full text |Cite
|
Sign up to set email alerts
|

Policy Design and Implementation of a New Public Rental Housing Management Scheme in China: A Step Forward or an Uncertain Fate?

Abstract: The management of the public rental sector has undergone tremendous change worldwide. Especially in China, given the large supply of public rental housing (PRH) in the short term, the management of PRH (PRHM) has been faced with a series of problems. The existing PRHM is unsustainable and a new scheme has been proposed. In this study we analyze whether this new scheme can solve the former management problems and achieve the reform objectives, so as to explore whether the new scheme can really improve the PRHM.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…And in practice, the management of PRH has been faced with a series of problems [49]. What is the affordability for residents under the PRH system?…”
Section: Discussionmentioning
confidence: 99%
“…And in practice, the management of PRH has been faced with a series of problems [49]. What is the affordability for residents under the PRH system?…”
Section: Discussionmentioning
confidence: 99%
“…In detail, inequitable allocation unit of PH, illegally subletting to third parties, and low tenancy turnover rate (Bo, 2012;Li et al, 2017;Xu & Luo, 2021;Zeng et al, 2017). Further, financial management issues that arise in PH include lack of operation and maintenance funding (Tu, 2017), insufficient funds generated by rental income to cover operating and capital expenses (Kushendar et al, 2021;Tu, 2017), and tenants who under economically disadvantaged group tend to default their rent payments and management fee (Luo et al, 2020). On top of that, social issues in PH include vandalism and high crime rates (Xu & Luo, 2021).…”
Section: The Rationale For Performance Measurement In Public Housingmentioning
confidence: 99%
“…White, 2013;Xu & Luo, 2021;Yuan et al, 2019). These issues arose as a consequence of mismanagement of property management (Luo et al, 2020;Priemus et al, 1999;Wei & Wang, 2021). To improve property management, performance measurement plays an important role to monitor the operation and current condition of the building to provide a clear direction on the parts that require further improvements (Hashim et al, 2015;A.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al [6] proposed a two-stage evolutionary high dimensional multi-objective optimization algorithm and designed a novel framework and process of public policy for the rental housing market. Luo [7] took China's public rental housing (PRH) as the research object and found that the wellintended housing policy mainly proposed three measures: government procurement, new financial arrangements and guided service contents. Furthermore, informed by ideas of social constructionism, which emphasises the politics of housing, McKee et al [8] emphasized the need for greater geographical sensitivity through an analysis of policy narratives.…”
Section: Literature Review On Housing Securitymentioning
confidence: 99%